Text-Based Modeling Strategy (TBMS) in Teaching Writing Skills: The Indonesian Context - Sudaryat, Yayat (EDUCARE, 2010)
ABSTRACT: This study was based on the issue that the Indonesia high school studentâs writing ability was still low. Therefore, it was needed to find out the factors causing the problem and solution to overcome in through the implementation of the Text-Based Modelling Strategy (TBMS). The study used the experimental methods with the Randomized Pretest-Posttest Comparison Group Design. The data were collected in the forms of essay, questionnaire, interviews result, document, and observation result. The main sources of the data were the students of SMA YAS (Sekolah Menengah Atas Yayasan Atikan Sunda or Senior High School of the Sundanese Education Foundation) in Bandung. Beside, the Indonesian teacher and some documents from the school saced as the additional source of the data. The result of this study proved that the TBMS could overcome the hindrance of writing, and it was also effective in increasing the students competence of writing an essay. The result was also valid for significance value of the essay writing aspectâs competence (substantive, textual, lexical, syntactic, and graphemic). Though they altogether increased the writing competence, it was seen that the TBMS was much better and more effectictive than the BMS (Basic Modeling Strategy) and CLS (Conventional Learning Strategy). The study found that the procedure composed and applied in the TBMS, that has never done before, contributed positively to the increasing of writing competence.KEY WORDS: Learning and teaching strategy, modeling, Text-Based Modelling Strategy, essays, and Â writing competence.About the Author: Dr. Yayat Sudaryat is a Lecturer at the Department of Sundanese Language Education, Faculty of Language and Art Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229, Bandung 40154, West Java, Indonesia. He can be reached at: kisudaryat_sunda@yahoo.comHow to cite this article? Sudaryat, Yayat. (2010). âText-Based Modeling Strategy (TBMS) in Teaching Writing Skills: The Indonesian Contextâ in EDUCARE: International Journal for Educational Studies, Vol.3(1) August, pp.85-102. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 25, 2010); Revised (July 25, 2010); and Published (August 17, 2010).